PENGEMBANGAN TEKNOLOGI PEMBELAJARAN PAI BERBASIS PESANTREN dI MA SYAMSUL HUDA - Humairah, Intan Balqis; Fathonah, Nurul; Acetylena, Sita (Dirasat: Journal Islamic Studies, 2025)
This study examines the implementation of Islamic Religious Education (PAI) learning at Islamic Boarding School (MA Syamsul Huda) with a focus on integrating traditional values and modern approaches. Using descriptive qualitative methods through in-depth interviews, participant observation, and document study, the study found that the developed learning model successfully combined classical Islamic boarding school methods (sorogan, bandongan, tahfizh) with modern learning techniques. However, the use of technology is still limited to basic tools such as projectors, facing infrastructure constraints and concerns about reducing the depth of religious understanding. Key findings indicate a gap between the needs of digital native students for technology-based interactive learning and teachers' preferences for traditional methods. The study identified significant potential for a blended learning model that combines face-to-face learning with digital content such as tahfizh applications, religious study videos, and virtual reality simulations. The results emphasize the importance of an evolutionary approach to technology integration, with recommendations for teacher training, infrastructure development, and the design of authentic digital content. The implications of this study indicate that the transformation of Islamic boarding school-based PAI learning in the digital era requires a balance between maintaining core values and adopting pedagogical innovation. These findings provide a conceptual framework for developing a model of religious education that maintains the character of Islamic boarding schools while being relevant to learning needs.